Therapeutic Anabolic and Anticatabolic Benefits of Natural Chinese Medicines for the Treatment of Osteoporosis - He, Jianbo; Li, Xiaojuan; Wang, Ziyi; Bennett, Samuel; Chen, Kai; Xiao, Zhifeng; Zhan, Jiheng; Chen, Shudong; Hou, Yu; Chen, Junhao; Wang, Shaofang; Xu, Jiake; et al. (Frontiers in Pharmacology, 2019)
Abstract: Osteoporosis is a bone disease characterized by increasing osseous fragility and fracture due to the reduced bone mass and microstructural degradation. Primary pharmacological strategies for the treatment of osteoporosis, hormone replacement (HRT) and alendronate therapies, may produce adverse side-effects and may not be recommended for long-term usage. Complementary and alternative medicines may provide effective treatment for osteoporosis without the risk of adverse side-effects. Current evidence suggests that natural herbs may be used to treat osteoporosis effectively and without adverse side-effects. Herbal therapies appear to improve bone metabolism, and attenuate the osteoporotic imbalance between bone formation and bone resorption at a cellular level by promoting osteoblast activity and inhibiting the effects of osteoclasts. Herbal therapies might therefore provide an effective and safer alternative to primary pharmacological strategies. The purpose of this article is to comprehensively review the natural Chinese herbs that have been reported with bone formation and anti-resorption effects, thus providing evidence for the use of natural herbal therapies to effectively treat osteoporosis.